Improving the psychological well-being of climacteric women through self-compassion training - Trisetyaningsih, Yanita; Hutasoit, Masta; Azizah, Fajriyati Nur (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: During the climacteric period, changes occur in a woman due to reduced estrogen levels. One of these changes is a change in psychological well-being (PWB), which impacts women's quality of life. Self-compassion training is needed to improve the ability to be compassionate towards oneself. The design of this training module will address three key aspects: self-kindness versus self-judgment, a sense of common humanity versus isolation, and mindfulness versus overidentification.  Objectives: This study aims to determine the effectiveness of self-compassion training in improving psychological well-being in women during climacteric periods.Methods: This study employs an action research approach with a single-group pretest and posttest experimental design (One Group Pretest-Posttest Design). The sample in this study was 59 respondents taken using a purposive sampling technique, with inclusion criteria including being willing to be respondents, aged 45-60 years old, not undergoing hormone replacement therapy, and still living with their husbands. Data analysis was carried out after the Psychological Well Being pretest and posttest data were collected, with the help of Statistical Product and Service Solution (SPSS) 17.0 release for Windows. Quantitative data analysis used a Parametric Statistics Paired Sample t-test, with a significance level set at p <0.05Results: Based on the study's results, it was found that the majority of respondents were aged 45-50 years, with 25 people (42.4%). Additionally, 30 people (50.8%) had two children, 76.3% were unemployed, and 72.9% had experienced menopause. The average psychological well-being pretest was 69.5, and the posttest was 79.8. Based on the results of the bivariate analysis, a significance value of 0.000 was obtained (p-value <0.05).Conclusions: There is a difference in psychological well-being before and after self-compassion intervention is given to climacteric women